2000
DOI: 10.1023/a:1008344528791
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of gemcitabine and epirubicin for the treatment of platinum-resistant or refractory advanced ovarian cancer

Abstract: The combination of gemcitabine 1000 mg/m2 (day 1, 8) and epirubicin at 60 mg/m2 (day 1) is a feasible therapy. Grade 4 neutropenia is frequent and G-CSF support is often required. With prophylactic support of G-CSF, the DLT is thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…It has been quickly elucidated that clinical symptoms moderately improved, but there was no real tumor-associated response. Subsequently, study groups focused their interest on reasonable combination therapy regimens with the well-tolerated gemcitabine [16][17][18][19][20][21][22][23][24][25][26]. The majority of study groups immediately performed phase II trials using fixed combination therapies, based on their experiences, and reported on response rates and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been quickly elucidated that clinical symptoms moderately improved, but there was no real tumor-associated response. Subsequently, study groups focused their interest on reasonable combination therapy regimens with the well-tolerated gemcitabine [16][17][18][19][20][21][22][23][24][25][26]. The majority of study groups immediately performed phase II trials using fixed combination therapies, based on their experiences, and reported on response rates and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Results of 31 phase I trials published between 1999 and 2000 have shown that it is essential to find the optimal dosage for combination therapy with other cytostatic drugs [12][13][14][15]. In various tumor types, gemcitabine has been combined with epirubicin [16][17][18], vinorelbine [19][20][21], oral uracil-tegafur [22] and multitargeted antifolate [23,24], for which well-tolerable combination chemotherapy protocols have been generated, but these regimens have not become relevant for pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gemcitabine has been combined in various tumor entities with epirubicin [16,50,69], vinorelbine [15,18,34], oral UFT [49], and the antifolate MTA [1,2], using well-tolerable protocols, but probably with no relevance for pancreatic carcinoma.…”
Section: Chemotherapymentioning
confidence: 99%
“…Several studies using GEM as a single agent in cisplatin-resistant patients have been performed with response rates of approximately 20% and well-tolerated hematological and non-hematological toxicity [8, 9, 10]. Given its mechanisms of action and favorable toxicity profile, combinations of GEM with other drugs (cisplatin, taxol, epirubicin or topotecan) have been explored in preclinical as well as clinical trials [11, 12, 13, 14]. In particular, a synergistic cytotoxic effect has been observed in human breast cancer cell lines when GEM was administered after doxorubicin [15].…”
Section: Introductionmentioning
confidence: 99%